Anthropogenic basin closure and groundwater salinization (ABCSAL) - Pauloo, Richard A.; Fogg, Graham E.; Guo, Zhilin; Harter, Thomas (Journal of hydrology (Amsterdam), 2021)
•Groundwater pumping may close a basin, leading to TDS accumulation in the aquifer.•We describe “Anthropogenic Basin Closure and groundwater SALinization” (ABCSAL).•We develop a model to estimate ongoing ABCSAL in California’s Tulare Basin.•Fundamentally, ABCSAL can only be reversed by opening the basin.•Salinization timescales are similar to those of aquifer depletion in the study site. Global food systems rely on irrigated agriculture, and most of these systems in turn depend on fresh sources of groundwater. In this study, we demonstrate that groundwater development, even without overdraft, can transform a fresh, open basin into an evaporation dominated, closed-basin system, such that most of the groundwater, rather than exiting via stream baseflow and lateral subsurface flow, exits predominantly by evapotranspiration from irrigated lands. In these newly closed hydrologic basins, just as in other closed basins, groundwater salinization is inevitable because dissolved solids cannot escape, and the basin is effectively converted into a salt sink. We first provide a conceptual model of this process, called “Anthropogenic Basin Closure and groundwater SALinization” (ABCSAL). We examine the temporal dynamics of ABCSAL using the Tulare Lake Basin, California, as a case study for a large irrigated agricultural region with Mediterranean climate, overlying an unconsolidated sedimentary aquifer system. Even with modern water management practices that arrest historic overdraft, results indicate that shallow aquifers (36 m deep) exceed maximum contaminant levels for total dissolved solids on decadal timescales. Intermediate (132 m) and deep aquifers (187 m), essential for drinking water and irrigated crops, are impacted within two to three centuries. Hence, ABCSAL resulting from groundwater development constitutes a largely unrecognized constraint on groundwater sustainable yield on similar timescales to aquifer depletion in the Tulare Lake Basin, and poses a serious challenge to groundwater quality sustainability, even when water levels are stable. Results suggest that agriculturally intensive groundwater basins worldwide may be susceptible to ABCSAL.